Healthy Aging: Comparative Analysis of Local Perception and Diet in Two Health Districts of Côte d’Ivoire and Japan - Bonfoh, B.; Koné, B. V.; Koffi, Y. D.; Miyama, T.; Fujimoto, Y.; Fokou, G.; Zinsstag, J.; Sugimura, R.; Makita, K. (Frontiers in Aging, 2022)
Context: Good health and longevity depend on dynamic interactions between biological, social, psychological, and environmental factors. Aging is globally a big challenge, particularly with the demographic transition, including population growth, and an emerging burden to society. Knowledge, behavior, diet, and consumption of animal source food were related to aging and emerged as the key factors modulating healthy aging. Objective: The study was designed to understand the main healthy aging factors, such as knowledge, social network, and diet of elders, and to derive mutual learning from it for healthy aging. Methods: A qualitative approach has been applied to explore health-related knowledge, attitude, and diet of elders from Ebetsu (Japan) and Tiassalé (Côte d’Ivoire) health districts, using focus group discussions and comparative context analysis between high- and low-income countries. Results: The study shows that living longer is a common feature of people in Japan compared to Côte d’Ivoire, where the life expectancy is still low. Both groups of elders have social networks that support them, and both offer their gained experience to society. While Japanese elders depend on pension and insurance for income and medical treatments, Ivorians depend mostly on their children and social network in old age. The worries of elders differ between the two regions. In Ebetsu, elder members of the community are concerned about the future burden they pose for the younger generation if they develop ill-health, making them more resilient to aging. In Taabo, elders are considered to be culturally and socially useful to the society. Elders in Ebetsu pointed out that for healthy aging, education on diet at a younger age, physical activities, and access to basic social services are the key aspects. This was not observed in Taabo’s context. Being inactive and dependent on others were described as the most worrying situations for elders in Ebetsu, as it is perceived to increase the risk of non-communicable diseases and anxiety. Elders in Ebetsu have good knowledge on what constitutes a healthy diet, and they believe that diversifying their diet, reducing portions, and substituting red meat with good animal and vegetable proteins are best eating practices to maintain good health. In Côte d’Ivoire, the diet is imbalanced and the whole family consumes the same meal made mainly with high-energy staples and little protein. However, it is observed in both societies that adopting a good diet is very expensive. Conclusion: The consciousness of aging is universal, but healthy aging varies according to the social systems, education, and knowledge on diet transition. Physical activities, protein–energy balance in diet, and social networks are the key for healthy aging in both contexts. The challenge is to find ways to increase knowledge regarding healthy aging and to strengthen the support system so that healthy aging becomes affordable.